Dangers of the chronic stress response in the context of the microbiota-gut-immune-brain axis and mental health: a narrative review - Warren, Alison; Nyavor, Yvonne; Beguelin, Aaron; Frame, Leigh A. (Frontiers in Immunology, 2024)
More than 20% of American adults live with a mental disorder, many of whom are treatment resistant or continue to experience symptoms. Other approaches are needed to improve mental health care, including prevention. The role of the microbiome has emerged as a central tenet in mental and physical health and their interconnectedness (well-being). Under normal conditions, a healthy microbiome promotes homeostasis within the host by maintaining intestinal and brain barrier integrity, thereby facilitating host well-being. Owing to the multidirectional crosstalk between the microbiome and neuro-endocrine-immune systems, dysbiosis within the microbiome is a main driver of immune-mediated systemic and neural inflammation that can promote disease progression and is detrimental to well-being broadly and mental health in particular. In predisposed individuals, immune dysregulation can shift to autoimmunity, especially in the presence of physical or psychological triggers. The chronic stress response involves the immune system, which is intimately involved with the gut microbiome, particularly in the process of immune education. This interconnection forms the microbiota-gut-immune-brain axis and promotes mental health or disorders. In this brief review, we aim to highlight the relationships between stress, mental health, and the gut microbiome, along with the ways in which dysbiosis and a dysregulated immune system can shift to an autoimmune response with concomitant neuropsychological consequences in the context of the microbiota-gut-immune-brain axis. Finally, we aim to review evidenced-based prevention strategies and potential therapeutic targets.